Reverse metabolomics for the discovery of chemical structures from humans - Gentry, Emily C.; Collins, Stephanie L.; Panitchpakdi, Morgan; Belda-Ferre, Pedro; Stewart, Allison K.; Carrillo Terrazas, Marvic; Lu, Hsueh-han; Zuffa, Simone; Yan, Tingting; Avila-Pacheco, Julian; Plichta, Damian R.; Aron, Allegra T.; et al. (Nature (London), 2024)
Determining the structure and phenotypic context of molecules detected in untargeted metabolomics experiments remains challenging. Here we present reverse metabolomics as a discovery strategy, whereby tandem mass spectrometry spectra acquired from newly synthesized compounds are searched for in public metabolomics datasets to uncover phenotypic associations. To demonstrate the concept, we broadly synthesized and explored multiple classes of metabolites in humans, including N -acyl amides, fatty acid esters of hydroxy fatty acids, bile acid esters and conjugated bile acids. Using repository-scale analysis 1 , 2 , we discovered that some conjugated bile acids are associated with inflammatory bowel disease (IBD). Validation using four distinct human IBD cohorts showed that cholic acids conjugated to Glu, Ile/Leu, Phe, Thr, Trp or Tyr are increased in Crohn’s disease. Several of these compounds and related structures affected pathways associated with IBD, such as interferon-γ production in CD4 + T cells 3 and agonism of the pregnane X receptor 4 . Culture of bacteria belonging to the Bifidobacterium , Clostridium and Enterococcus genera produced these bile amidates. Because searching repositories with tandem mass spectrometry spectra has only recently become possible, this reverse metabolomics approach can now be used as a general strategy to discover other molecules from human and animal ecosystems. A new discovery strategy, ‘reverse metabolomics’, facilitates high-throughput matching of mass spectrometry spectra in public untargeted metabolomics datasets, and a proof-of-concept experiment identified an association between microbial bile amidates and inflammatory bowel disease.